On Griess Algebras - Roitman, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
In this paper we prove that for any commutative (but in general non-associative) algebra A with an invariant symmetric non-degenerate bilinear form there is a graded vertex algebra V = V₀ + V₂ + V₃ + ..., such that dim V₀ = 1 and V₂ contains A. We can choose V so that if A has a unit e, then 2e is the Virasoro element of V, and if G is a finite group of automorphisms of A, then G acts on V as well. In addition, the algebra V can be chosen with a non-degenerate invariant bilinear form, in which case it is simple.